Efficacy of immune checkpoint inhibitor as maintenance therapy for advanced or metastatic cancers: A meta-analysis of randomized controlled trials. Issue 38 (23rd September 2022) - Mo, Dun-Chang; Huang, Jian-Feng; Luo, Peng-Hui; Huang, Shang-Xiao; Wang, Han-Lei
Abstract : Background: This study aimed to evaluate the efficacy of immune checkpoint inhibitors (ICIs) as maintenance therapy for advanced or metastatic cancers. Methods: The PubMed, Embase, and Cochrane Library databases were searched for eligible randomized controlled trials. A meta-analysis of eligible studies investigating the outcomes including progression-free survival (PFS), overall survival (OS), and objective response rate (ORR) with a significance level set to 0.05 was performed. Results: Five RCTs (n = 2828) were identified in this analysis. The pooled hazard ratios (HRs) of PFS and OS for ICI maintenance therapy were 0.88 (95% CI: 0.68–1.13, P  = .31) and 0.82 (95% confidence interval [CI]: 0.74–0.92, P  = .0005), respectively; the pooled odds ratio (OR) of ORR was 2.24 (95% CI: 1.23–4.09, P  = .0008). Subgroup analysis indicated that anti-PD-L1 antibody significantly improved the OS ( P  = .0008), while anti-PD-1 and anti-PD-1 plus anti-cytotoxic T lymphocyte antigen 4 antibodies significantly prolonged the PFS of patients. Conclusion: ICI maintenance therapy enhanced the survival of patients with advanced or metastatic cancers.